F12 Abnormal regulation of macrophage-derived transforming growth factor: β 1 (TGF-β1) production in Huntington disease. (29th August 2012) - Di Pardo, A; Alberti, S; Concetti, F; Elifani, F; Martino, T; Busceti, CL; Battaglia, G; Maglione, V; Amico, E; Squitieri, F
Abstract : Background: Huntington's Disease (HD) is a neurodegenerative disorder caused by a trinucleotide repeat (CAG) expansion within Huntingtin gene (HTT) that results in a polyglutamine (polyQ) stretch in N-terminal region of huntingtin (Htt). Mutant Htt (mHtt) interfers with several molecular pathways, including cell signalling, transcriptional regulation, axonal transport and neurotrophins production and release. Emerging evidence indicates that reduced levels of neurotrophic factors, including brain derived neurotrophic factor and transforming growth factor-β 1 (TGF-β1) are linked to the pathogenesis of HD. Previous study from our lab and collaborators, demonstrated that TGF-β1 levels varied throughout disease course in both central and peripheral tissues with a significant reduction at early stage of the disease. Aim: Our aim was to clarify the contribution of each whole blood cell subset at producing TGF-β1 in the periphery and to determine whether TGF-β1 may have potential utility as a marker of disease progression. Methods: Monocytes-derived macrophages from 81 HD individuals and age-matched healthy controls (n=30) were analysed by flow cytometry for the determination of TGF-β1 production. Immunohistochemical analyses were carried out for the examination of TGF-β1 expression in HD post mortem brain tissues. Results: Our results indicated that the frequency of TGF-β1 expressing macrophages was significantly reduced in presymptomatic and I stage HD subjects compared to controls and increased with disease progression. Similar results were observed in HD brain tissues. Conclusion: Here we demonstrated that macrophages showed variable TGF-β1 production profile during disease progression. These data correlated well with TGF-β1 immunoreactivity in HD brain tissues. Collectively we described an interesting link between production of TGF-β1 in the periphery and central defect and highlighted the potential of TGF-β1 as a possible novel marker for disease progression.